2009
DOI: 10.1002/eji.200838933
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium chelonae sensitisation induces CD4+‐mediated cytotoxicity against BCG

Abstract: Significant variability in efficacy of live Mycobacterium bovis BCG as a tuberculosis vaccine is observed globally. Effects of pre-vaccination sensitisation to non-tuberculous environmental mycobacteria (Env) are suspected to underlie this phenomenon, but the mechanisms remain unclear. We postulated that it could be due to Env-specific T cells exerting cytotoxicity against BCG-infected host cells. After murine sensitisation with heat-killed antigens of different Env species, splenocytes from M. chelonae (CHE)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…2A). In our previous work [9], however, we had shown that post-BCG-splenic IFN-␥ production by ELISA was similar between sensitized and nonsensitized mice. Splenic IL-10 concentrations were lower 3 weeks after BCG administration (Fig.…”
Section: Resultsmentioning
confidence: 80%
“…2A). In our previous work [9], however, we had shown that post-BCG-splenic IFN-␥ production by ELISA was similar between sensitized and nonsensitized mice. Splenic IL-10 concentrations were lower 3 weeks after BCG administration (Fig.…”
Section: Resultsmentioning
confidence: 80%